Comparative Study of Ambiguity Resolution between the Efficiency of Conventional and Islamic Banks in a Stable Financial Context - Haddad, Achraf; El Ammari, Anis; Bouri, Abdelfettah (International Journal of Economics and Financial Issues, 2019)
Based on the weak results of previous researches on the efficiency's topic of Islamic and classical banks, we noticed that they were paradoxical results which are sometimes complementary and sometimes contradictory. Several studies have confirmed the effectiveness and resilience of Islamic banks in the face of financial shocks and crises during periods of disruption and financial imbalances, while others have supported the priority of conventional banks. Each stream of research has defended its contextual visions by the necessary specific arguments. But during the economic stable periods the question does not have the answer so far. In this article, two samples were taken from two reference populations of all existing classical and Islamic banks in the selected countries. The choice of banks is limited to countries whose banking systems incorporate both Islamic and conventional banks regardless of the proportion of each system in the country's banking market. Subsequently, each list bank was reduced on the basis of qualitative and quantitative filtering criteria. Therefore, each conventional bank has its closest Islamic equivalence in terms of capital and size taken from the same country. Consequently, the sample size was reduced to 63 banks each over the period (2010-2018). The banks selected form the two samples are all large and listed in different stock exchanges around the world. The results of our research showed that theoretically Islamic finance is enjoying a growing reputation, as it is considered potentially an ethical finance. However, empirically, Islamic banks are less efficient than their conventional counterparts during a financial stable period. Keywords: Conventional banks, Islamic banks, Efficiency, Comparative study, Financial stable period. JEL Classifications: F33, G20, G21, G24, G30. DOI: https://doi.org/10.32479/ijefi.8623